Effect of Geometric Transmission Error on Load and Vibration Characteristic of Spiral Bevel Gear - Bohui Yang; Xuemei Cao; Dingjun She; Haoyang Tian (Jixie chuandong)
The tooth surface grid node coordinates are accurately calculated by the tooth surface equation. According to the density requirements of the grid nodes， the grid nodes are evenly divided， the tooth root transition curve mesh is encrypted， and the finite element software is directly imported to generate an accurate finite element model of the spiral bevel gear meshing transmission. Tooth surfaces with different geometric transmission errors are designed， and the loaded tooth contact analysis is performed by using finite element software，and the contact stress and loaded transmission error of gear pairs with different geometric transmission errors are analyzed. Based on the modal superposition method， the vibration response analysis of the spiral bevel gear is used to obtain the vibration displacement， velocity， acceleration. The comparison results show that under the load of 200 N·m， as the geometric transmission error increases， the degree of edge contact decreases， the fluctuation of the upper and lower amplitudes of the loaded transmission error decreases by 44%， and the corresponding vibration displacement， speed and acceleration decrease， effectively reduce deformation and vibration.